Development of Pteridophyte Taxonomic Learning Resource to Foster Cognitive and Psychomotor Learning Outcomes (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2022)
Authentic learning resources are meaningful for Biology learning, particularly in conceiving Plantae topic. The availability of plants, especially Pteridophyte in school environment is very limited and require more adequate plant learning resources. This study aimed to develop a Pteridophytes Taxonomic Learning Resource (PTLR) and tested its validity, practicality, and effectiveness. Research and Development were done refers to the ADDIE model. The PTLR was validated by a taxonomist and instructional media expert. The practicality was observed from the responses of teachers and students, while the effectiveness was explored based on cognitive and psychomotor learning outcomes. The PTLR was developed by container gardening method with 29 fern species representing the classes of Pteridophyte and showed specific characteristics which organized in their taxonomic groups. The results showed that PTLR is very valid with average score of 85.5% and considered practical by teachers (81.25%) and students (90.65%). The PTLR was also effective in achieving two basic competencies by Curriculum of 2013 of Biology with cognitive outcome N-gain of 0.57 (moderate) and psychomotor 86.34% (very good). In summing up, the PTLR is recommended as a learning resource of Plantae topic at senior high school. This research result enriches the types of innovative biology learning resources.